KLON GEN PENISILIN ASILASE PADA COSMID pHC79 - Linar Z. Udin; Hadi Sutedjo (Jurnal Kimia Terapan Indonesia, 1996)
Penicillin acylase plays an important role in the catalysis of benzylpenicillin hydrolytic reaction, prodeucing 6-aminopenicilanic acid (6- APA), a precursorfor the formation of penicillinderivatives. Cloning of the penicillin acylase gene of Escherichia coli B130 chromosomal DNA on pHC79 cosmid vector to increase the enzyme activity has been investigated. The cloning was cooducted with several steps, including isolation of the chromosomal DNA. digestion by restriction enzyme, ligation by T4-DNA ligase, transformation of the recombinant DNA, and selection of the transformans. Microbial assay utilizing Serratia marcescens was carried out for screening the penicillin acylase colony, whereas the determination of the enzyme activity was examined based on Kornfeld method. From 2070 colonies screened by S. marcescens, only 4 positive colonies were obtained. The enzyme activity of these colonies was 4-6 fold higher than the penicillin acylase activity from E. coli B 130.